2010
DOI: 10.1073/pnas.1000446107
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state functional MRI in depression unmasks increased connectivity between networks via the dorsal nexus

Abstract: To better understand intrinsic brain connections in major depression, we used a neuroimaging technique that measures resting state functional connectivity using functional MRI (fMRI). Three different brain networks-the cognitive control network, default mode network, and affective network-were investigated. Compared with controls, in depressed subjects each of these three networks had increased connectivity to the same bilateral dorsal medial prefrontal cortex region, an area that we term the dorsal nexus. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

93
923
11
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,059 publications
(1,036 citation statements)
references
References 37 publications
93
923
11
9
Order By: Relevance
“…Correlation maps were produced by extracting the BOLD time course from a seed region (10-mm sphere each), and then computing the correlation coefficient between that time course and the time course from all other brain voxels. Based on data from previous connectivity studies (Fox et al, 2006;Sheline et al, 2010;McCarthy et al, 2013), the left and right subgenual anterior cingulate cortex (ACC; 7x ÂŒ 10, yÂŒ 35, z ÂŒ2) was extracted as the seed region of interest from the affective network that was modulated between ToM trials and NULL events; and the left and right precuneus ( 7x ÂŒ7, yÂŒ À60, z ÂŒ 21) as the seed region of interest in the DMN during NULL events. Thus, the DMN was modulated during rest (NULL events) and the ToM network was modulated by functional variation in ToM and NULL events.…”
Section: Functional Coupling Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Correlation maps were produced by extracting the BOLD time course from a seed region (10-mm sphere each), and then computing the correlation coefficient between that time course and the time course from all other brain voxels. Based on data from previous connectivity studies (Fox et al, 2006;Sheline et al, 2010;McCarthy et al, 2013), the left and right subgenual anterior cingulate cortex (ACC; 7x ÂŒ 10, yÂŒ 35, z ÂŒ2) was extracted as the seed region of interest from the affective network that was modulated between ToM trials and NULL events; and the left and right precuneus ( 7x ÂŒ7, yÂŒ À60, z ÂŒ 21) as the seed region of interest in the DMN during NULL events. Thus, the DMN was modulated during rest (NULL events) and the ToM network was modulated by functional variation in ToM and NULL events.…”
Section: Functional Coupling Analysismentioning
confidence: 99%
“…As we use the term here, functional connectivity describes the relationship between different brain regions and within particular networks by assessing the correlation of their neuronal activity (Nierhaus et al, 2012). Regions within one particular neural network, the default mode network (DMN), have been found to display their greatest levels of activity when at rest, and decreased activity in some DMN sub-regions during task-based stimulation (Sheline et al, 2010;Zhang and Li, 2012b). During these periods of "active rest", the DMN is thought to be involved in internal processes such as selfreferential processing, inner speech, emotional control, episodic memory, and ToM processes (Spreng et al, 2009;Wolf et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vmPFC not only represents a core region of the DMN (Buckner et al., 2008), but it is also a critical region involved in self‐referential processing (Lemogne, Delaveau, Freton, Guionnet, & Fossati, 2012; Northoff et al., 2006). This finding suggests hyperconnectivity within the DMN in patients with MDD, and is consistent with previous studies in patients with depression (Alexopoulos et al., 2012; Kaiser, Andrews‐Hanna, Wager, & Pizzagalli, 2015; Sheline, Price, Yan, & Mintun, 2010) (but see de Kwaasteniet et al. (2015) and Zhu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The DMN, consisting of the posterior cingulate cortex and medial prefrontal cortex (PFC) as its core areas [65,66] and the precuneus and temporo-parietal cortices, underlies the psychological process of introspection-the mind turning internally as it moves away from externally-concentrated thoughts [67][68][69]. A majority of studies have demonstrated that the DMN is hyperactive in MDD [70,71], and this may account for the rumination states in MDD [72]. The CCN, consisting of the dorsolateral PFC and pregenual ACC [73,74], is thought to be involved in the top-down modulation of attention and the regulation of emotional responses [75,76].…”
Section: Mr Imaging Of Resting-state Functional Connectivitymentioning
confidence: 99%